Pengembangan E-Modul Berbasis Proyek untuk Meningkatkan Minat Belajar Siswa SMP - Khasanah, Reza Miftakhul; Avianty, Donna (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research aims to develop e-modules based on Project-Based Learning (PjBL) on spatial geometry material for junior high school students to increase learning interest. The e-module development was carried out using the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. This research was piloted at MTS Al Huda Putri Malang with 20 research subjects of eighth grade junior high school students. The validity of the e-module was tested through assessments by material experts and media experts, while the effectiveness of the product was evaluated based on the increase in students' learning interest before and after using the e-module. The data collection technique used an expert validation sheet and a Likert-scale-based student learning interest questionnaire. The data analysis technique was carried out descriptively quantitatively by calculating the percentage of e-module feasibility and comparing the average score of students' learning interest at the pre- and post-implementation stages. The results showed that the project-based e-module was declared valid with a validation score of 84.44% from material experts and 90% from media experts, and was suitable for use without major revisions. The effectiveness of the e-module was shown by an increase in students' learning interest from the